Antagonism and mycoparasitism potential of Trichoderma spp. on some of the major soil borne pathogens of soybean - X.B. YANG, SHRISHAIL S. NAVI, A.H. RAJASAB* and (Indian Phytopathology, 2016)
In an in vitro dual culture plug technique, a single 6-mm culture plug of actively growing cultures of Colletotrichum truncatum, Fusarium virguliforme, Macrophomina phaseolina, Pythium irregulare, Rhizoctonia solani, and Sclerotinia sclerotiorum were placed inverted on one end inside periphery of 9-cm PDA plates and on the opposite end 6-mm culture plug of either Trichoderma hamatum (T1-03) or T. koningiopsis (T2-10). Against Septoria glycines (SG), culture plug of T1-03 or T2-10 were placed in the center of pre-spread SG spore suspension PDA plates. Both T1-03 and T2-10 significantly (P